Molecular taxonomy of two sympatric sibling species of the pollenbeetle genus Meligethes (Coleoptera: Nitidulidae) - de Biase, Alessio; Antonini, Gloria; Mancini, Emiliano; Audisio, Paolo (Zootaxa, 2003)
A molecular analysis was performed, combined with field data on insect/host-plant associations, in order to clarify taxonomic relationships within the W-Palaearctic Meligethes aeneus complex (Coleoptera, Nitidulidae, Meligethinae). The analysis was focused on the specific distinction of M. aeneus (Fabricius, 1775), and M. gracilis C.Brisout de Barneville, 1863, with special regard to populations occurring in sympatry. The genetic divergence between the two examined taxa, based on comparison between mtDNA sequence data, was congruent with distance values usually scored between related, but evidently separated, insect species. Genetic data and ecological evidence clearly show that Meligethes aeneus and M. gracilis, erroneously synonymized in a recent paper by a Russian author, are distinct biological species that frequently occur in syntopy in Western Europe.